Detection and clinical relevance of Staphylococcus aureus nasal carriage: an update. Issue 1 (January 2014) - Verhoeven, Paul O; Gagnaire, Julie; Botelho-Nevers, Elisabeth; Grattard, Florence; Carricajo, Anne; Lucht, Frédéric; Pozzetto, Bruno; Berthelot, Philippe
<x xml:space="preserve">Abstract</x> Staphylococcus aureus nasal carriage is a well-defined risk factor of infection with this bacterium. The increased risk of S. aureus infection in nasal carriers is supported by the fact that the strains isolated from both colonization and infection sites are indistinguishable in most of the cases. Persistent nasal carriage seems to be associated with an increased risk of infection and this status could be defined now in clinical routine by using one or two quantitative nasal samples. There is evidence for supporting the detection of nasal carriage of S. aureus in patients undergoing cardiac surgery and in those undergoing hemodialysis in order to implement decolonization measures. More studies are needed to determine which carriers have the highest risk of infection and why decolonization strategies failed to reduce S. aureus infection in some other groups of patients.